Ethnic Differences in C-Reactive Protein Concentrations - Kelley-Hedgepeth, Alyson; Lloyd-Jones, Donald M; Colvin, Alicia; Matthews, Karen A; Johnston, Janet; Sowers, MaryFran R; Sternfeld, Barbara; Pasternak, Richard C; Chae, Claudia U; SWAN Investigators (Clinical chemistry (Baltimore, Md.), 2008)
Background: Limited data exist regarding the ethnic differences in C-reactive protein (CRP) concentrations, an inflammatory marker associated with risk of cardiovascular disease (CVD). We hypothesized that known CVD risk factors, including anthropometric characteristics, would explain much of the observed ethnic variation in CRP. Methods: We performed a cross-sectional analysis of 3154 women, without known CVD and not receiving hormone therapy, enrolled in the Study of Women’s Health Across the Nation (SWAN), a multiethnic prospective study of pre- and perimenopausal women. Results: The study population was 47.4% white, 27.7% African-American, 8.5% Hispanic, 7.7% Chinese, and 8.6% Japanese; mean age was 46.2 years. African-American women had the highest median CRP concentrations (3.2 mg/L), followed by Hispanic (2.3 mg/L), white (1.5 mg/L), Chinese (0.7 mg/L), and Japanese (0.5 mg/L) women (all pairwise P < 0.001 compared with white women). Body mass index (BMI) markedly attenuated the association between ethnicity and CRP. After adjusting for age, socioeconomic status, BMI, and other risk factors, African-American ethnicity was associated with CRP concentrations >3 mg/L (odds ratio 1.37, 95% CI 1.07–1.75), whereas Chinese and Japanese ethnicities were inversely related (0.58, 0.35–0.95, and 0.43, 0.26–0.72, respectively). Conclusions: Modifiable risk factors, particularly BMI, account for much but not all of the ethnic differences in CRP concentrations. Further study is needed of these ethnic differences and their implications for the use of CRP in CVD risk prediction.